Предмет: Математика,
автор: dotaulmar
( 2 x − 1 )( 1 5 + 9 x )−6x( 3 x + 5 )=1 0 2
Ответы
Автор ответа:
1
Ответ:
х= -13
Пошаговое объяснение:
Откроем скобки:
30х+18х²-15-9х-18х²-30х=102
Решим все, что можно:
-15-9х=102
числа с х перенесем на лево, известные числа–на право:
-9х=102+15
-9х=117
х=117÷(-9)
х= -13
Похожие вопросы
Предмет: Русский язык,
автор: 896775654
Предмет: Русский язык,
автор: ganis554
Предмет: Русский язык,
автор: ник3948
Предмет: Другие предметы,
автор: klychkovamarina
Предмет: Математика,
автор: Veruvya